The Tandem of Liquid Chromatography and Network Pharmacology for the Chemical Profiling of Pule'an Tablets and the Prediction of Mechanism of Action in Treating Prostatitis - Hui Zhuge; Zhiwei Ge; Jiaojiao Wang; Jianbiao Yao; Jiayu He; Yi Wang; Yingchao Wang; Yu Tang (MDPI AG, 2023)
Prostatitis, a prevalent urinary tract disorder in males, has a complex etiology that leads to severe clinical discomfort. Pule'an Tablets, a classic single-component formulation primarily based on rapeseed pollen, have been clinically proven to have a beneficial therapeutic effect on both prostatitis and benign prostatic hyperplasia. However, there is currently a lack of research on the chemical composition and mechanisms of action of Pule'an Tablets in treating prostatitis. In this study, using liquid chromatography-mass spectrometry (LC-MS), a total of 53 compounds in Pule'an Tablets were identified, including flavonoids, phenylpropionamides, lipids, glucosinolates, and nucleic acids. Subsequently, through a network pharmacology analysis, potential target genes and their mechanisms of action were predicted accordingly. The results suggested that genes such as LPAR5, LPAR6, LPAR4, LPAR3, LPAR2, LPAR1, F2, ENPP2, MMP9, and TNF, along with pathways like prostate cancer, endocrine resistance, bladder cancer, and the IL-17 signaling pathway, may represent potential pathways involved in the therapeutic effects of Pule'an Tablets. This study represents the first systematic investigation into the chemical composition of Pule'an Tablets, shedding light on the potential mechanisms underlying their efficacy in treating prostatitis. These findings could serve as a valuable reference for future pharmacological research on Pule'an Tablets.